Microwave dielectric properties of wooden cross-arms - Khalid, Kaida; Sahri, Mohd Hamami; Keong, Ng Kok; Fuad, Syed Ahmad
When wooden poles and cross-arms are exposed to weather, its surface undergoes changes such warping, loss of some surface fibers and surface roughing. As a result of weathering its unprotected surface tends to absorb more moisture as compare to the surface of sound wood. After the rain, the moisture will sustain in the weathered wood for some time before it is dried out. There is a possibility to relate the quality of the wooden cross-arms with the amount of its moisture content (MC) at a particular time. This work deals with the effect of weather on the dielectric properties of wooden cross-arms. The samples from sound wood, incipient decay and decay woods were chosen for dielectric study with frequency ranging from 0.2 GHz to 20 GHz. It is found that the decay wood can absorbed more than 70% MC (dry-basis) as compare to sound wood of only about 30% MC. The results of the dielectric measurement are compared with the values predicted by dielectric mixture equations. From the above study, there is a great possibility of using microwave reflection method to determine the moisture content and condition of wooden cross-arms.